SOSIALISASI TEKNOLOGI MEDIA PEMBELAJARAN DIGITAL UNTUK GURU SMP AL HIKAM KEMAYORAN BANGKALAN - Jovianto, Kevin Piyu Gareth; Rosidah, Devi Zumrotir; Fauzi, Irsyad; Afifah, Rohmatul; Sari, Dian Inka; Syarifudin, Albitar; Setyawan, Arief; Sumriyah, Sumriyah (Politeknik Perkeretaapian Indonesia Madiun, 2025)
The socialization of technology-based learning media at SMP Al Hikam Kemayoran aims to improve the capacity of teachers in utilizing website-based media as a learning aid. This activity focuses on introducing new media that can increase the variety and appeal of materials and motivate students to be more active in class. The socialization began with a survey through Mentimeter to find out the media that teachers have used. The results showed that although some common media have been used, there is still a need for more varied media that are in accordance with the digital era. The speaker introduced various application and website-based media, although challenges arose due to school policies that limit the use of digital devices by students. The speaker suggested that the policy on the use of gadgets in class be considered carefully, considering the effectiveness of digital media in increasing student interaction and learning motivation.